Self-organization of nanoneedles in Fe/GaAs (001) epitaxial thin film - Huang, Y; Wang, S; Wang, C; Xie, Z; Cockayne, D; Ward, R (2006)
Well-aligned nanoneedles are found to form in a FeGaAs (001) epitaxial thin film when irradiated with a Ga+ ion beam normal to the sample surface at an ion dose of 3× 1017 cm2 in a focused ion beam. These nanoneedles, with their axes perpendicular to the original sample surface, are composed of GaAs nanorods with Fe nanoislands situated at the top. The GaAs nanorods, formed from the GaAs substrate, are crystalline and in the same crystal orientation as the GaAs substrate. The crystalline nature of the Fe thin film is disrupted by the ion sputtering, becoming nanocrystalline Fe islands. It is the thin Fe layer that is responsible for the formation of the nanoneedles. The ion sputtering of the Fe layer roughens the sample surface due to the uneven sputtering rate of the Fe layer. The removal of the Fe layer exposes the substrate to the incident ions, which then sputter the substrate leading to the formation of the nanoneedles. © 2006 American Institute of Physics.